Indonesian Language Teachers' Skills to Write Academic Articles in Reputable Journals - Indrya Mulyaningsih; Nurul Azmi; Bagaskara Nur Rochmansyah; Nana Priajana (Ranah: Jurnal Kajian Bahasa, 2024)
Teachers are fundamentally required to have pedagogical, personality, social, and professional competencies. One of their continuing professional competencies is to conduct academic publications. This study aims to explore academic publications in journals conducted by Indonesian language subject teachers at the high school level in Three Regions of Cirebon and the factors affecting them. The data were obtained by interviewing 138 out of 152 teachers because some school principals did not allow the interview and no permission letter from the National Unity and Political Agency, especially in Cirebon City. The interview results show that 35% of teachers have never published in Academic journals. This condition is partly due to the following factors: a) time, b) the purpose of the journal, c) lack of confidence, d) difficulty in researching online, e) age approaching retirement, f) technology stuttering, g) not accustomed to writing, h) lack of motivation, i) need approval from the supervisor, j) lack of knowledge on how to create an article, k) there is no demand and l) availability of funds. Therefore, there needs to be efforts from several parties, especially the school community. For example, the Subject Teacher Conference (MGMP) activities can also be utilized to introduce and familiarize teachers with Academic publications. School principals provide facilities for teachers to be able to conduct academic publications. AbstrakGuru pada dasarnya dituntut memiliki kompetensi pedagogik, kepribadian, sosial, dan profesional. Salah satu kompetensi profesional berkelanjutan mereka adalah melakukan publikasi akademik. Penelitian ini bertujuan untuk mengetahui publikasi akademik pada jurnal yang dilakukan oleh guru mata pelajaran bahasa Indonesia tingkat SMA di Wilayah III Cirebon dan faktor-faktor yang mempengaruhinya. Data diperoleh dengan mewawancarai 138 dari 152 guru karena beberapa kepala sekolah tidak mengizinkan wawancara dan tidak ada surat izin dari Badan Kesatuan Bangsa dan Politik khususnya di Kota Cirebon. Hasil wawancara menunjukkan bahwa 35% guru belum pernah mempublikasikan di jurnal Akademik. Kondisi ini antara lain disebabkan oleh beberapa faktor berikut: a) waktu, b) tujuan jurnal, c) kurang percaya diri, d) kesulitan melakukan riset online, e) usia mendekati pensiun, f) gagap teknologi, g) belum terbiasa untuk menulis, h) kurangnya motivasi, i) perlu persetujuan dosen pembimbing, j) kurangnya pengetahuan tentang cara membuat artikel, k) tidak ada permintaan dan l) ketersediaan dana. Oleh karena itu, perlu adanya upaya dari beberapa pihak khususnya warga sekolah. Misalnya saja kegiatan Konferensi Guru Mata Pelajaran (MGMP) juga dapat dimanfaatkan untuk mengenalkan dan membiasakan guru terhadap publikasi Akademik. Kepala sekolah memberikan fasilitas kepada guru untuk dapat melakukan publikasi akademik